Detection of Hb variants and hemoglobinopathies in Indian population using HPLC: Report of 2600 cases - Sachdev Ritesh; Dam Arpita; Tyagi Gaurav (Wolters Kluwer Medknow Publications, 2010)
Background: Inherited abnormalities of hemoglobin synthesis include a myriad of disorders ranging from thalassemia syndromes to structurally abnormal hemoglobin variants. Identification of these disorders is immensely important epidemiologically and aid in prevention of more serious hemoglobin disorders. Aims: High performance liquid chromatography (HPLC) forms an important tool for accurate and speedy diagnosis of various hemoglobin disorders. About 2600 cases have been studied for identification of various hemoglobin disorders in Indian population. Material and Methods: The study was performed on BIORAD VARIANT using beta thalassemia short program. Results and conclusion: Abnormal hemoglobin fractions on HPLC were seen in 327 of the 2,600 cases displayed. Of this, the beta thalassemia trait was the predominant abnormality with a total of 232 cases (8.9%). There were 15(0.6%) cases of beta thalassemia major and 16 of thalassemia intermedia. The rest comprised of Hb D Punjab (13 cases; 0.5%), Elevated Hb F (25 cases; 0.9%), Hb E (seven cases including two Hb E homozygous and five Hb E heterozygous), Double heterozygous Hb E-beta thal trait (six cases), Hb Q India (five cases), Double heterozygous Hb Q India -beta thal trait (two cases), Hb S (total cases three including one Hb S homozygous; two Hb S -beta thal trait) and one case each of Hb J Meerut, Hb D-Iran and Hb Lepore trait. Detection of this abnormal hemoglobin, particularly keeping in mind a high prevalence of Hb A2, will help in prevention of more serious hemoglobinopathies including beta thalassemia major. HPLC forms a rapid and accurate tool in early detection and management of various hemoglobin disorders.